Hinged surgical instruments: efficacy of double manual cleaning versus automated cleaning on biofilm removal. (June 2022) - de Melo Costa, D.; Castillo, R.; Vickery, K.; Ferreira Veiga Tipple, A.; de Oliveira Lopes, L.K.; Hu, H.
Summary: The efficacy of double manual cleaning (DMC) with enzymatic detergent followed by alkaline detergent on biofilm removal on hinged surgical instruments was compared to automated cleaning. Biofilm-covered haemostatic forceps were divided into four groups: positive control (soaked in sterile water); DMC; DMC plus extra brushing of the inner hinge; and automated cleaning. All DMC, DMC plus brushing the hinge, and automated cleaning significantly ( P < 0.001) reduced 94.8%, 99.8%, and 100% viable bacteria and 82.3%, 93.8%, and 95.1% residual protein, respectively, compared to positive control. DMC instruments had significantly more viable bacteria ( P < 0.05) and residual protein ( P < 0.01) than those in instruments subjected to DMC with hinge brushing and automated cleaning. However, there was no significant difference in residual protein between DMC with hinge brushing and automated cleaning. In sterilizing service units with no access to automated cleaning equipment, it is important to brush the inner hinge during manual cleaning, and DMC plus brushing the inner hinge could be considered a viable alternative for cleaning hinged surgical instruments.